Analys av HCN-emission från kometen C/2013 R1 (Lovejoy) - Olivefors, Astrid; Källström, Philip; Tegehall, Elin; Levinsson, Alexander (My University, 2015)
In this report, results from the observations of comet C/2013 R1 (Lovejoy) carried out with the 20 meter telescope at Onsala Space Observatory during the autumn of 2013 are presented. The project comprises the analysis of data from the observation dates when emission from the rotational transition J = 1 0 for the molecule hydrogen cyanide (HCN) were observed. Detections have been made for seven different dates when C/2013 R1 (Lovejoy) were at a distance of 0.94-0.82AU from the sun, just before perihelion. The production rate increases from 31026 s1 to 51026 s1 with the decreasing distance to the sun. One of the days has also been divided in mean value formations over shorter time intervals for which a periodic variation in the production rate can be discerned although not confirmed. To perform calculations and processing of data, two computer programs have been used. The first is xs, a data reduction software for radio astronomical observations, written by Per Bergman at Onsala Space Observatory. The second program is mom, developed by Stefanie Milam at NASA Goddard Space Flight Center. iv
Keywords: Klimatforskning; Energi; Grundläggande vetenskaper; Meteorologi och atmosfärforskning; Climate Research; Energy; Basic Sciences; Meteorology and Atmospheric Sciences